Interactions between macro-nutrients’ intake, FTO and IRX3 gene expression, and FTO genotype in obese and overweight male adolescents - Doaei, Saeid (Adipocyte, 2019)
This study is the first to identify the effects of FTO genotype on the interactions between the level of macro-nutrients intake and the expression level of fat mass and obesity associated (FTO) and homeobox transcription factor iriquois-3 (IRX3) genes This longitudinal study was carried out on 84 overweight and obese adolescent boys in Tehran, Iran. The rs9930506 SNP in FTO was genotyped at baseline and the level of FTO and IRX3 expression in PBMCs and macro-nutrients’ intake were assessed at baseline and after 18 weeks of the intervention. The results identified that the higher carbohydrates intake significantly up-regulated the FTO gene (P = 0.001) and down-regulated the IRX3 gene (P = 0.01). Protein intake up-regulated the FTO gene (P = 0.001). In carriers of GG genotype of FTO gene, the amount of dietary carbohydrate had a positive association with FTO gene expression (p = 0.001, and p = 0.04, respectively). In AA/AG carriers, dietary protein was positively associated with FTO gene expression (p = 0.001) and dietary carbohydrate was negatively associated with IRX3 gene expression (P = 0.04). Therefore, dietary carbohydrateseems to be associated with FTO and IRX3 genes expression. These associations are influenced by FTO genotype.